Composite seed layer and preparation method thereof, TGV glass plate and preparation method thereof, and chip
By using the preparation method of composite seed layer on the TGV glass plate, the problems of complex copper plating process and poor bonding effect are solved, and the effective connection between the copper plating layer and the glass substrate are realized and the preparation process is simplified.
Patent Information
- Application Number
- CN202411812208.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The copper plating process of existing TGV glass plates is complicated, and the bonding effect of the copper layer with the intermediate layer and glass substrate is poor.
The preparation method of the composite seed layer is adopted, including soaking the glass substrate in a titanium-containing treatment solution, drying it, and depositing it in a zinc-containing treatment solution, followed by heat treatment and copper plating in an electroless plating bath to form a composite seed layer of the copper-plated glass substrate.
Through the designed seed layer structure, the adhesion between the seed layer, glass substrate and copper-plated layer is improved, and the effective connection between the copper-plated layer and the glass substrate is achieved, the preparation process is simplified, and the use effect of TGV glass plate is improved.
Smart Images

Figure CN119725223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of copper plating of TGV glass plates, and specifically to a composite seed layer and a preparation method, a TGV glass plate and a preparation method, and a chip, and in particular to a composite seed layer and a preparation method for copper-plated TGV glass plates, a copper-plated TGV glass plate and a preparation method, and a chip. Background Art
[0002] At present, in semiconductor and microelectronic packaging technology, through-glass via (TGV) technology is widely used in optoelectronic integration, microelectromechanical systems (MEMS) and high-frequency communication equipment due to its excellent electrical properties, optical properties and thermal stability.
[0003] For example, CN113066758A discloses a TGV deep hole filling method, which includes the following steps: A. cleaning a glass substrate; B. laser drilling a glass substrate to obtain a plurality of glass through holes; C. corroding the glass substrate and the glass through holes with a corrosive liquid; D. sputtering a seed layer on the glass substrate and the glass through holes; E. immersing the glass substrate in a dilute sulfuric acid solution for activation; and F. electroplating.
[0004] However, the glass surface itself has chemical inertness and smooth surface characteristics, which will limit its physical and chemical bonding with other materials. Therefore, improving the adhesion between glass and metal or other materials becomes the key. However, the current filling process still has defects such as complex process and poor bonding between the copper layer and the intermediate layer and glass substrate after electroplating filling. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a composite seed layer and preparation method, a TGV glass plate and preparation method, and a chip to solve the defects of the complicated preparation process of the copper-plated TGV glass plate and the poor bonding effect of the copper layer, the intermediate layer, and the glass substrate.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite seed layer, the preparation method comprising:
[0008] The glass substrate is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for at least one deposition to obtain an intermediate treated substrate;
[0009] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in sequence to obtain a composite seed layer of the copper-plated glass substrate.
[0010] The composite seed layer provided by the present invention has a designed seed layer structure obtained by adopting a specific preparation process. With the help of the coupling effect between the layers, the adhesion between the seed layer, the glass substrate and the copper-plated layer is improved, and the effective connection between the copper-plated layer and the glass substrate is achieved, effectively ensuring the use effect of the TGV glass plate.
[0011] As a preferred technical solution of the present invention, the solute used to prepare the titanium-containing treatment liquid includes: one or a combination of at least two of di(triethanolamine)diisopropyl titanate, di(acetylacetonato)diisopropyl titanate, bis(acetylacetonato)titanium oxide, tetrakis(dimethylamino)titanium, tetraisopropyl titanate or triisostearate isopropyl titanate.
[0012] Preferably, the solvent used to prepare the titanium-containing treatment liquid includes one or a combination of at least two of isopropanol, ethanol or petroleum ether.
[0013] Preferably, the mass concentration of the solute in the titanium-containing treatment solution is 0.1-10%.
[0014] As a preferred technical solution of the present invention, the soaking treatment time is 2-60s.
[0015] Preferably, the drying temperature is 50-200°C.
[0016] As a preferred technical solution of the present invention, the preparation process of the zinc-containing treatment solution is as follows: adding alkali to a zinc salt solution, and then adding a coupling agent and water to obtain the zinc-containing treatment solution.
[0017] Preferably, the base comprises an alkaline solution.
[0018] Preferably, the alkaline solution comprises: one or a combination of at least two of aqueous ammonia, potassium hydroxide solution or sodium hydroxide solution.
[0019] Preferably, the mass concentration of the alkaline solution is 10-50%.
[0020] Preferably, the concentration of the zinc salt solution is 0.1-5 mol / L.
[0021] Preferably, the volume ratio of the alkaline solution to the zinc salt solution is 1:(0.1-0.8).
[0022] Preferably, the volume ratio of the alkaline solution to water is 1:(10-40).
[0023] Preferably, the volume concentration of the coupling agent in the zinc-containing treatment solution is 1-5%.
[0024] Preferably, the coupling agent comprises: one or a combination of at least two of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, methoxy fluorine-containing silane, aminosilylfluoroalkane or trifluoropropylmethyldimethoxysilane.
[0025] As a preferred technical solution of the present invention, the deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water for deposition.
[0026] Preferably, the temperature of the hot water is 85-99°C.
[0027] Preferably, the deposition is performed 3-30 times.
[0028] Preferably, the thickness of the zinc oxide layer obtained by deposition is 100-500 nm.
[0029] As a preferred technical solution of the present invention, the temperature of the heat treatment is 350-600°C.
[0030] Preferably, the heat treatment time is 0.5-1.5h.
[0031] Preferably, the copper plating method includes electroless copper plating.
[0032] Preferably, the copper layer obtained by copper plating has a thickness of 0.4-1 μm.
[0033] In a second aspect, the present invention provides a composite seed layer, wherein the composite seed layer is obtained by the preparation method described in the first aspect.
[0034] In a third aspect, the present invention provides a TGV glass plate, wherein the TGV glass plate comprises the composite seed layer as described in the second aspect.
[0035] In a fourth aspect, the present invention provides a method for preparing the TGV glass plate according to the third aspect, the method comprising:
[0036] The composite seed layer of the copper-plated glass substrate is electroplated with copper to obtain a TGV glass plate.
[0037] In a fifth aspect, the present invention provides a chip, comprising the composite seed layer as described in the second aspect.
[0038] Compared with the prior art solutions, the present invention has the following beneficial effects:
[0039] (1) The seed layer provided by the present invention can improve the bonding strength of the glass substrate, and the bonding strength can change with the number of metal oxide layers. As long as the appropriate temperature is reached, there is no need to control humidity, pH and other conditions.
[0040] (2) The seed layer provided by the present invention does not block holes or cause bubbles during the preparation process. The bonding strength between the seed layer having a thickness of 200-500 nm and the copper layer can reach above 2.48 N / cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a SEM photograph of the zinc oxide layer obtained in Example 1 of the present invention;
[0042] Figure 2 This is a backlight test photograph of the seed layer obtained after copper plating in Example 1 of the present invention;
[0043] Figure 3 is a SEM photograph of a TGV glass plate formed by electroplating copper on the seed layer obtained in Example 1 of the present invention;
[0044] Figure 4 is a SEM photograph of the seed layer obtained in Example 1 of the present invention;
[0045] Figure 5 This is a composition diagram of the Spectrum1 site of the SEM photograph of the seed layer obtained in Example 1 of the present invention;
[0046] Figure 6 This is a composition diagram of the Spectrum2 site of the SEM photograph of the seed layer obtained in Example 1 of the present invention;
[0047] Figure 7 This is a composition diagram of the Spectrum3 site of the SEM photograph of the seed layer obtained in Example 1 of the present invention;
[0048] Figure 8 This is a composition diagram of the Spectrum 4 site of the SEM photograph of the seed layer obtained in Example 1 of the present invention.
[0049] In the figure: Spectrum1 corresponds to the glass substrate, Spectrum2 corresponds to the layer obtained by ZnO deposition, Spectrum3 corresponds to the copper layer obtained by copper plating in an electroless plating bath, and Spectrum3 corresponds to the copper layer obtained by electroplating copper.
[0050] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION
[0051] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:
[0052] This embodiment provides a composite seed layer, which is obtained by the following preparation method, wherein the preparation method comprises:
[0053] The glass substrate is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for at least one deposition to obtain an intermediate treated substrate;
[0054] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in sequence to obtain a composite seed layer of the copper-plated glass substrate.
[0055] In the present invention, the glass substrate refers to a smooth glass plate, or a glass plate containing processed structures such as grooves, blind holes, and through holes.
[0056] In this embodiment, the glass substrate may be selectively cleaned before the immersion treatment, such as plasma cleaning, dry gas purging, laser cleaning, acid cleaning, surfactant cleaning, etc., to clean the glass substrate to ensure that subsequent treatment can be carried out effectively. The cleaning standard can be selected and designed according to the conventional requirements in the field.
[0057] Among them, the solute used to prepare the titanium-containing treatment liquid includes: one or a combination of at least two of di(triethanolamine)diisopropyl titanate, di(acetylacetonato)diisopropyl titanate, bis(acetylacetonato)titanium oxide, tetrakis(dimethylamino)titanium, tetraisopropyl titanate or triisostearate isopropyl titanate.
[0058] Exemplarily, the combination of solutes used to prepare the titanium-containing treatment liquid is such as: a combination of di(triethanolamine)diisopropyl titanate and di(acetylacetonato)diisopropyl titanate, a combination of bis(acetylacetonato)titanium oxide and tetrakis(dimethylamino)titanium, and a combination of tetraisopropyl titanate and triisostearate isopropyl titanate.
[0059] Wherein, the solvent used to prepare the titanium-containing treatment liquid includes one or a combination of at least two of isopropanol, ethanol or petroleum ether.
[0060] Illustratively, the combination of solvents includes: a combination of isopropanol and ethanol, a combination of isopropanol and petroleum ether, a combination of ethanol and petroleum ether, and the like.
[0061] Among them, the mass concentration of the solute in the titanium-containing treatment liquid is 0.1-10%, for example, it can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values within this range also meet the requirements.
[0062] The immersion time is 2-60s, for example, 2s, 5s, 10s, 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s or 60s, but is not limited to the listed values. Other values not listed within the range also meet the requirements.
[0063] Wherein, the drying temperature is 50-200°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0064] In the present invention, the purpose of drying is to remove the solvent in the di(triethanolamine)titanate diisopropyl solution attached to the surface of the substrate after the immersion treatment, so as to retain the solute.
[0065] The preparation process of the zinc-containing treatment solution is as follows: adding alkali to a zinc salt solution, and then adding a coupling agent and water to obtain the zinc-containing treatment solution.
[0066] Wherein, the alkali comprises an alkali solution.
[0067] Wherein, the alkaline solution includes: one or a combination of at least two of ammonia water, potassium hydroxide solution or sodium hydroxide solution.
[0068] Illustratively, the combination of bases includes: a combination of aqueous ammonia and potassium hydroxide solution, a combination of potassium hydroxide solution and sodium hydroxide solution, a combination of sodium hydroxide solution and potassium hydroxide solution, and the like.
[0069] Wherein, the mass concentration of the alkaline solution is 10-50%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 26.2%, 26.4%, 26.6%, 26.8%, 27%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, etc., but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0070] The alkali may also be selectively added as a solid alkali, and the amount of the solid alkali added is designed and selected based on the concentration of the alkali solution and the volume ratio in the preparation process.
[0071] Wherein, the concentration of the zinc salt solution is 0.1-5mol / L, for example, it can be 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.42mol / L, 0.44mol / L, 0.46mol / L, 0.48mol / L, 0.5mol / L, 0.52mol / L, 0.54mol / L, 0.56mol / L, 0.58mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L or 5mol / L, but is not limited to the listed values, and other values not listed within this range also meet the requirements.
[0072] In the present invention, the zinc salt used in the zinc salt solution includes soluble zinc salts such as zinc sulfate, zinc chloride, zinc nitrate, etc., and the solvent is a commonly used solvent in the art such as water.
[0073] Wherein, the volume ratio of the alkaline solution to the zinc salt solution is 1:(0.1-0.8), for example, it can be 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75 or 1:0.8, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0074] Wherein, the volume ratio of the alkaline solution to water is 1:(10-40), for example, it can be 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:21, 1:22, 1:23, 1:24, 1:26, 1:28, 1:30, 1:32, 1:34, 1:36, 1:38 or 1:40, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0075] Wherein, the volume concentration of the coupling agent in the zinc-containing treatment solution is 1-5%, for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or 5%, etc., but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0076] Wherein, the coupling agent includes: one or a combination of at least two of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, methoxy fluorine-containing silane, aminosilyl fluorine alkane or trifluoropropylmethyldimethoxysilane.
[0077] Exemplarily, the combination of coupling agents includes: a combination of γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, a combination of methoxy fluorine-containing silane and aminosiloxane, a combination of aminosiloxane and trifluoropropylmethyldimethoxysilane, and the like.
[0078] Wherein, the deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water for deposition.
[0079] The temperature of the hot water is 85-99°C, for example, it can be 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, 96°C, 97°C, 98°C or 99°C, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0080] Wherein, the deposition is performed 3-30 times, for example, 3 times, 4 times, 5 times, 6 times, 8 times, 10 times, 12 times, 14 times, 16 times, 18 times, 20 times, 22 times, 24 times, 26 times, 28 times or 30 times, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0081] In the present invention, deposition once means that the substrate is immersed in a zinc-containing treatment solution and then placed in hot water for deposition. Deposition multiple times means repeating the above deposition process once.
[0082] The thickness of the deposited zinc oxide layer is 100-500 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0083] In the present invention, the thickness of the zinc oxide layer obtained by deposition refers to the total thickness of the zinc oxide layer obtained after all the depositions for a specified number of times.
[0084] Wherein, the temperature of the heat treatment is 350-600°C, for example, it can be 350°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0085] The heat treatment time is 0.5-1.5h, for example, it can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h or 1.5h, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0086] Wherein, the copper plating method includes electroless copper plating.
[0087] The thickness of the copper layer obtained by copper plating is 0.4-1 μm, for example, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0088] In the present invention, the relevant control parameters of copper plating by means of an electroless plating bath can be selected according to the conventional technical requirements in the art to ensure that the thickness of the copper layer obtained by copper plating as defined in the present invention is achieved.
[0089] Exemplarily, the operating pH value of the electroless copper plating bath is 10-13, for example, it can be 10, 10.5, 11, 11.5, 12, 12.5 or 13, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0090] Exemplarily, the operating temperature of the electroless copper plating bath is 30-35°C, for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0091] In the present invention, the plating solution used in the electroless copper plating bath can be any plating solution commonly used in the art, as long as the copper plating effect of the present invention can be achieved.
[0092] Furthermore, the present invention provides a composite seed layer obtained by the aforementioned preparation method.
[0093] Furthermore, the present invention provides a TGV glass plate, wherein the TGV glass plate comprises the composite seed layer as described above.
[0094] Furthermore, the present invention provides a method for preparing the aforementioned TGV glass plate, the method comprising:
[0095] The composite seed layer of the copper-plated glass substrate is electroplated with copper to obtain a TGV glass plate.
[0096] In the present invention, the copper electroplating process after the composite seed layer is formed can be specifically based on the conventional copper electroplating process in the art, as long as the hole can be filled.
[0097] Furthermore, the present invention provides a chip, comprising the composite seed layer as described above.
[0098] Further, in order to illustrate the good bonding effect that can be achieved by the composite seed layer provided by the present invention when the TGV glass plate is copper plated, the following practical examples are used for illustration, as follows:
[0099] Example 1
[0100] This embodiment provides a method for preparing a composite seed layer, the preparation method comprising:
[0101] The glass substrate (glass substrate with through holes, i.e., TGV glass substrate) is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for deposition 5 times to obtain an intermediate treatment substrate;
[0102] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in an electroless plating bath in sequence to obtain a composite seed layer of a copper-plated glass substrate;
[0103] The titanium-containing treatment liquid is a di(triethanolamine)titanate diisopropyl ester solution with a mass concentration of 0.5%, the solvent used is isopropanol, the immersion treatment time is 60s, and the drying temperature is 100°C;
[0104] The preparation process of the zinc-containing treatment liquid is as follows: adding ammonia water with a mass concentration of 26.5% to a zinc salt (zinc sulfate) solution with a concentration of 0.5 mol / L, and then adding a coupling agent (γ-aminopropyltriethoxysilane) and water to obtain a zinc-containing treatment liquid; the volume ratio of ammonia water to the zinc salt solution is 1:0.27, and the volume ratio of ammonia water to water is 1:22; the volume concentration of the coupling agent in the zinc-containing treatment liquid is 1.5%;
[0105] The deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water at 90° C. for deposition, wherein the thickness of the deposited zinc oxide layer is 100 nm;
[0106] The heat treatment temperature is 450°C and the time is 1.4h;
[0107] The working pH value of the electroless copper plating bath is 12, the working temperature is 35° C., and the thickness of the copper layer obtained by the electroless copper plating bath is 0.4 μm.
[0108] Figure 1 Schematic diagram of zinc oxide after deposition. Figure 2 The backlight test image of the seed layer obtained after copper plating shows that no hole blocking phenomenon is found in the TGV glass with a pore size of 50μm; Figure 3 This is a SEM photo of the TGV glass plate formed by electroplating copper on the seed layer. No hole blocking was found, which can further confirm that there was no hole blocking in the backlight test; Figure 4This is a SEM photo of the seed layer obtained in Example 1 of the present invention. Figure 4 The component analysis diagrams corresponding to Spectrum1, Spectrum2, Spectrum3 and Spectrum4 are shown in Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown, the corresponding element results are shown in Table 1, Table 2, Table 3 and Table 4.
[0109] Table 1
[0110] Spectrum1
[0111]
[0112] Table 2
[0113] Spectrum2
[0114]
[0115] Table 3
[0116] Spectrum3
[0117]
[0118] Table 4
[0119] Spectrum4
[0120]
[0121] It can be seen from the figures and tables that the zinc oxide layer obtained in the seed layer obtained in the present invention contains a certain amount of Ti, that is, the bonding performance is improved through the coupling effect of Zn and Ti; among them, the elements that appear in the test results of Spectrum2, Spectrum3 and Spectrum4 in the figures and tables and coincide with the composition of the glass substrate are due to the inevitable glass debris that occurs during the sample preparation process.
[0122] Example 2
[0123] This embodiment provides a method for preparing a composite seed layer, the preparation method comprising:
[0124] The glass substrate (glass substrate with through holes, i.e., TGV glass substrate) is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for 10 depositions to obtain an intermediate treatment substrate;
[0125] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in an electroless plating bath in sequence to obtain a composite seed layer of a copper-plated glass substrate;
[0126] The titanium-containing treatment liquid is a diisopropyl di(acetylacetonato)titanate solution with a mass concentration of 0.8%, the solvent used is ethanol, the soaking treatment time is 30 seconds, and the drying temperature is 90°C;
[0127] The preparation process of the zinc-containing treatment liquid is as follows: adding ammonia water with a mass concentration of 26.5% to a zinc salt (zinc nitrate) solution with a concentration of 0.5 mol / L, and then adding a coupling agent (γ-methacryloxypropyltrimethoxysilane) and water to obtain a zinc-containing treatment liquid; the volume ratio of ammonia water to the zinc salt solution is 1:0.28, and the volume ratio of ammonia water to water is 1:23; the volume concentration of the coupling agent in the zinc-containing treatment liquid is 1.8%;
[0128] The deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water at 92° C. for deposition, wherein the thickness of the deposited zinc oxide layer is 200 nm;
[0129] The heat treatment temperature is 500°C and the time is 1.2h;
[0130] The working pH value of the electroless copper plating bath is 12, the working temperature is 33° C., and the thickness of the copper layer obtained by the electroless copper plating bath is 0.5 μm.
[0131] Example 3
[0132] This embodiment provides a method for preparing a composite seed layer, the preparation method comprising:
[0133] The glass substrate (glass substrate with through holes, i.e., TGV glass substrate) is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for 20 depositions to obtain an intermediate treatment substrate;
[0134] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in an electroless plating bath in sequence to obtain a composite seed layer of a copper-plated glass substrate;
[0135] The titanium-containing treatment liquid is a tetraisopropyl titanate solution with a mass concentration of 0.1%, the solvent used is petroleum ether, the soaking treatment time is 60 seconds, and the drying temperature is 100°C;
[0136] The preparation process of the zinc-containing treatment liquid is as follows: adding ammonia water with a mass concentration of 26% to a zinc salt (zinc sulfate) solution with a concentration of 0.4 mol / L, and then adding a coupling agent (methoxy fluorinated silane) and water to obtain a zinc-containing treatment liquid; the volume ratio of ammonia water to the zinc salt solution is 1:0.25, and the volume ratio of ammonia water to water is 1:20; the volume concentration of the coupling agent in the zinc-containing treatment liquid is 5%;
[0137] The deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water at 85° C. for deposition, wherein the thickness of the deposited zinc oxide layer is 400 nm;
[0138] The heat treatment temperature is 400°C and the time is 1.5h;
[0139] The working pH value of the electroless copper plating bath is 12.5, the working temperature is 33.5° C., and the thickness of the copper layer obtained by the electroless copper plating bath is 0.5 μm.
[0140] Example 4
[0141] This embodiment provides a method for preparing a composite seed layer, the preparation method comprising:
[0142] The glass substrate (glass substrate with through holes, i.e., TGV glass substrate) is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for 30 depositions to obtain an intermediate treatment substrate;
[0143] The obtained intermediate processed substrate is subjected to heat treatment and copper plating in an electroless plating bath in sequence to obtain a composite seed layer of a copper-plated glass substrate;
[0144] The titanium-containing treatment liquid is a diisopropyl di(triethanolamine)titanate solution with a mass concentration of 10%, the solvent used is isopropanol, the immersion treatment time is 10s, and the drying temperature is 60°C;
[0145] The preparation process of the zinc-containing treatment liquid is as follows: a sodium hydroxide solution with a mass concentration of 50% is added to a zinc salt (zinc chloride) solution with a concentration of 0.6 mol / L, and then a coupling agent (trifluoropropylmethyldimethoxysilane) and water are added to obtain a zinc-containing treatment liquid; the volume ratio of ammonia water to the zinc salt solution is 1:0.3, and the volume ratio of ammonia water to water is 1:24; the volume concentration of the coupling agent in the zinc-containing treatment liquid is 1%;
[0146] The deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water at 95° C. for deposition, wherein the thickness of the deposited zinc oxide layer is 500 nm;
[0147] The heat treatment temperature is 550°C and the time is 1h;
[0148] The working pH value of the electroless copper plating bath is 13, the working temperature is 35° C., and the thickness of the copper layer obtained by the electroless copper plating bath is 0.6 μm.
[0149] Comparative Example 1
[0150] The only difference from Example 1 is that the zinc oxide is not immersed in a titanium-containing treatment solution during the preparation process. If the zinc oxide is not immersed in a titanium solution, the zinc oxide will be deposited unevenly, resulting in bubbling after electroplating, which is not conducive to the detection of bonding strength.
[0151] Comparative Example 2
[0152] The only difference from Example 1 is that no deposition is performed during the preparation process. Without the deposition of the zinc oxide layer, the bonding strength becomes poor, and the baking and bubbling after electroplating are not conducive to the detection of the bonding strength.
[0153] Example 5
[0154] The only difference from Example 1 is that no heat treatment is performed.
[0155] Example 6
[0156] The only difference from Example 1 is that no coupling agent is added to the zinc-containing treatment solution. Not adding a coupling agent results in bubbling during chemical copper deposition, which makes the bonding strength worse and is not conducive to the detection of the bonding strength.
[0157] Example 7
[0158] The only difference from Example 1 is that the deposition was performed 10 times.
[0159] Example 8
[0160] The only difference from Example 1 is that the deposition was performed 20 times.
[0161] Example 9
[0162] The only difference from Example 1 is that the deposition was performed 30 times.
[0163] The composite seed layer obtained in the above example was electroplated with a 20 μm copper layer at a current density of 2.0 ASD, and then annealed at 250° C. for 30 min. The adhesion performance test and reflow test were performed. The adhesion performance test was carried out using a peel strength tester. The results are detailed in Table 5 below.
[0164] Table 5
[0165] Adhesion force / N / cm Reflow test Example 1 2.48 The bonding force remains unchanged and there is no delamination Example 2 4.37 The bonding force remains unchanged and there is no delamination Example 3 7.70 The bonding force remains unchanged and there is no delamination Example 4 11.00 The bonding force remains unchanged and there is no delamination Comparative Example 1 / Bubbling, stratification Comparative Example 2 / Bubbling, stratification Example 5 0.30 Bubbling, stratification Example 6 / Bubbling, stratification Example 7 3.86 The bonding force remains unchanged and there is no delamination Example 8 7.12 The bonding force remains unchanged and there is no delamination Example 9 10.00 The bonding force remains unchanged and there is no delamination
[0166] It can be seen from Table 5 that the bonding force in the solution provided by the present invention can change with the thickness of the oxide. The higher the number of oxide layers, the denser the needle-shaped crystals formed after sintering, which is more conducive to enhancing the bonding force.
[0167] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0168] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0169] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a composite seed layer, characterized in that: The preparation method comprises: The glass substrate is placed in a titanium-containing treatment solution for immersion treatment, and after drying, is placed in a zinc-containing treatment solution for at least one deposition to obtain an intermediate treated substrate; The obtained intermediate processed substrate is subjected to heat treatment and copper plating in sequence to obtain a composite seed layer of a copper-plated glass substrate.
2. The preparation method according to claim 1, characterized in that The solute used to prepare the titanium-containing treatment liquid includes: one or a combination of at least two of di(triethanolamine)diisopropyl titanate, di(acetylacetonato)diisopropyl titanate, bis(acetylacetonato)titanium oxide, tetrakis(dimethylamino)titanium, tetraisopropyl titanate or triisostearate isopropyl titanate; Preferably, the solvent used to prepare the titanium-containing treatment liquid includes one or a combination of at least two of isopropanol, ethanol or petroleum ether; Preferably, the mass concentration of the solute in the titanium-containing treatment solution is 0.1-10%.
3. The preparation method according to claim 1 or 2, characterized in that: The soaking time is 2-60s; Preferably, the drying temperature is 50-200°C.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation process of the zinc-containing treatment solution is as follows: adding alkali to a zinc salt solution, and then adding a coupling agent and water to obtain a zinc-containing treatment solution; Preferably, the base comprises an alkaline solution; Preferably, the alkaline solution comprises: one or a combination of at least two of aqueous ammonia, potassium hydroxide solution or sodium hydroxide solution; Preferably, the mass concentration of the alkaline solution is 10-50%; Preferably, the concentration of the zinc salt solution is 0.1-5 mol / L; Preferably, the volume ratio of the alkaline solution to the zinc salt solution is 1:(0.1-0.8); Preferably, the volume ratio of the alkaline solution to water is 1:(10-40); Preferably, the volume concentration of the coupling agent in the zinc-containing treatment solution is 1-5%; Preferably, the coupling agent comprises: one or a combination of at least two of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, methoxy fluorine-containing silane, aminosilylfluoroalkane or trifluoropropylmethyldimethoxysilane.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The deposition comprises: placing the substrate soaked in the zinc-containing treatment solution in hot water for deposition; Preferably, the temperature of the hot water is 85-99°C; Preferably, the deposition is performed 3-30 times; Preferably, the thickness of the zinc oxide layer obtained by deposition is 100-500 nm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the heat treatment is 350-600°C; Preferably, the heat treatment time is 0.5-1.5h; Preferably, the copper plating method includes electroless copper plating bath; Preferably, the copper layer obtained by copper plating has a thickness of 0.4-1 μm.
7. A composite seed layer, characterized in that: The composite seed layer is obtained by the preparation method according to any one of claims 1 to 6.
8. A TGV glass plate, characterized in that: The TGV glass sheet comprises the composite seed layer as claimed in claim 7.
9. A method for preparing a TGV glass plate as claimed in claim 8, characterized in that: The preparation method comprises: The composite seed layer of the copper-plated glass substrate is electroplated with copper to obtain a TGV glass plate.
10. A chip, characterized in that: The chip comprises the composite seed layer as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
TGV deep hole filling method
CN113066758A